2019
DOI: 10.1186/s41231-019-0036-5
|View full text |Cite
|
Sign up to set email alerts
|

Prunus armeniaca effects on expression of genes related to apoptosis in human breast cancer cells

Abstract: Background: Apoptosis inhibition depends on the balance between expression of some regulatory genes including Bax and c-FLIP, despite breast cancer has long been associated with disturbances in apoptosis regulation. The objective of present study was to determine the expression levels of Bax and c-FLIP mRNAs in 1 μg sample of total RNA obtained from MCF7 and MDA-MB-231 human breast cancer cells treated with Prunus armeniaca extract. Methods: Prunus armeniaca effect was measured by MTT assay with different drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…Consequently they suspected that PA could be related to anti-apoptotic genes inhibition in Human breast cancer. (Mahmoudi et al, 2019) An animal study performed on rabbits contradicted our results and stated that the apricot seeds contents, amygdalin, might have a potential risk on animal health as it caused microscopic structure changes in their livers. Nevertheless, this study couldn't verify the toxic effect in relation to the highest dose supplied (Kolesárová et al, 2020) On the other hand, Cassiem & Kock in 2019 reported that there was an intra S-phase block in the cell cycle of human colon cancer cells in vitro after been treated with South African kernel extract.…”
Section: Apoptosis Andnecrosiscontrasting
confidence: 75%
See 2 more Smart Citations
“…Consequently they suspected that PA could be related to anti-apoptotic genes inhibition in Human breast cancer. (Mahmoudi et al, 2019) An animal study performed on rabbits contradicted our results and stated that the apricot seeds contents, amygdalin, might have a potential risk on animal health as it caused microscopic structure changes in their livers. Nevertheless, this study couldn't verify the toxic effect in relation to the highest dose supplied (Kolesárová et al, 2020) On the other hand, Cassiem & Kock in 2019 reported that there was an intra S-phase block in the cell cycle of human colon cancer cells in vitro after been treated with South African kernel extract.…”
Section: Apoptosis Andnecrosiscontrasting
confidence: 75%
“…Hence recent cancer research is directed towards dysregulation of apoptosis being the beginning of carcinogenesis. Number of studies revealed the signi cant role that apoptosis play in tumorigeneses (Mahmoudi et al, 2019) Minaiyan et al, performed a study on rats, where they induced ulcerative colitis and treated it with PA comparing it with prednisolone as the standard treatment. Their results showed improve effect in the PA group especially with those treated intraperitoneal than those treated orally.…”
Section: Apoptosis Andnecrosismentioning
confidence: 99%
See 1 more Smart Citation
“…There is not enough evidence to support the therapeutic effects of PA, thus this area is still being researched. Therefore, the purpose of this research is to assess PA extract's impact on OSCC (Mahmoudi et al, 2019).…”
Section: (Fratianni Et Al 2018)mentioning
confidence: 99%
“…An extract from apricots significantly inhibited the proliferation of MCF-7, HDF, and MDA-MB-231 human breast cancer cells in a concentration-dependent manner after 24, 48, and 72 h. The IC 50 values of this extract against MCF7, HDF, and MDA-MB-231 cells after 72 h were 0.5, 1.51, and 0.48 mg/mL, respectively. The expression levels of Bax and c-FLIP regulatory genes, obtained from the total RNA of MCF-7 and MDA-MB-231 cells, were reduced in the presence of the extract in a time-dependent manner [ 87 ].…”
Section: Anticancer Activities: Underlying Multi-targets Mechanismsmentioning
confidence: 99%